Application of whey protein isolates and zein for the formulation of alginate-based delivery systems encapsulating Ganoderma lucidum polyphenols - Y. Wang; I. Špoljarić; G. Mršić; Petra Veršec; Jasmina Vučilovski; Draženka Komes; Ana Belščak-Cvitanović; Aleksandra Vojvodić; Arijana Bušić; S. Karlović (Croatian Journal of Food Science and Technology, 2016)
Due to the rich phytochemical composition of the medicinal mushroom Ganoderma lucidum, especially its ß-glucan-based polysaccharides and triterpenes, but polyphenols, amino acids, and proteins as well, Ganoderma is often used in various nutraceutical and functional food products. Lately these products have been formulated with microencapsulated forms of active compounds in order to prevent their degradation after oral consumption and under processing conditions. The aim of this study was to characterize and encapsulate polyphenols from the aqueous extract of Ganoderma, using ionic gelation of alginate (A) and its combination with whey protein isolates (WPI) and zein (Z). The obtained hydrogel beads were scanned for physico-chemical and morphological properties, encapsulation efficiency of polyphenols, and their release kinetics in simulated gastrointestinal fluids. The addition of WPI to the alginate resulted in the reduction of the particle size and the spherical shape of the beads, while beads formulated with zein were characterized as larger, with irregular morphology. Encapsulation efficiency of total polyphenols has been determined as follows: 76.91% (A-WPI) < 83.91% (A) < 85.42% (A-Z). The most extended release of polyphenols in simulated gastrointestinal fluids has been achieved by employing WPI in the alginate delivery system. The implementation of additional coatings resulted in the enhanced properties of plain alginate carrier, where alginate-based hydrogels immobilizing Ganoderma polyphenols proved to be potential functional ingredients.